2016
DOI: 10.1007/s00421-016-3394-y
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variability in the patterns of responses for electromyography and mechanomyography during cycle ergometry using an RPE-clamp model

Abstract: The results of the present study indicated that there were differences between composite and individual patterns of responses for EMG and MMG parameters during moderate and heavy cycle ergometry at a constant RPE. Thus, composite models did not represent the unique muscle activation strategies exhibited by individual responses when cycling in the moderate and heavy intensity domains when using an RPE-clamp model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…Similar evidence for unique sensory tolerance between individuals was demonstrated by Cochrane‐Snyman et al. (), who observed large degrees of inter‐individual variability for the patterns of MMG response when subjects performed cycling exercise at a constant level of perceived exertion. In this context, it is interesting to consider the individualistic rate of change in force twitch kinetics together with the stimulation of group III/IV muscle afferents in regards to failure times during fatiguing exercise.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Similar evidence for unique sensory tolerance between individuals was demonstrated by Cochrane‐Snyman et al. (), who observed large degrees of inter‐individual variability for the patterns of MMG response when subjects performed cycling exercise at a constant level of perceived exertion. In this context, it is interesting to consider the individualistic rate of change in force twitch kinetics together with the stimulation of group III/IV muscle afferents in regards to failure times during fatiguing exercise.…”
Section: Discussionsupporting
confidence: 77%
“…; Cochrane‐Snyman et al. ; Cè et al. ) have suggested that the MMG response during fatiguing exercise may support the muscle wisdom hypothesis (Marsden et al.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations